1961
DOI: 10.1139/v61-022
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Isotope Effect in the Amination of Chlorobenzene by Sodamide

Abstract: WIixt~rres of chlorobenzene and chloroben~ene-2-~H have been subjected to partial amination by sodamide in liquid ammonia and both the unreacted starting material and the product aniline have been analyzed for deuterium. Deuterium in the aniline is distributed approximately equally between the ortho and lneta positions. The results give strong support to the niecha~lisrn proposed by Roberts and co-workers in which the slow step is the formation of an intermediate, such as benzyne, which is symnietrical with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1961
1961
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Thus The same results were observed with chlorobenzene-l-14 C, bromobenzene-1-14 C, and iodobenzene-l-14 C, and in deuterated bromobenzene it was found that the percentage of deuterium increased with percentage of reaction [505]. Fluorobenzene-2-D exchanged deuterium with the solvent very rapidly [506]. In dilute solution for partial reaction chlorobenzene-2-D showed a small increase in deuterium content, but showed a decrease in deuterium content in concentrated solutions.…”
Section: Solvolysis and The Effect Of Solvent On Ratessupporting
confidence: 78%
“…Thus The same results were observed with chlorobenzene-l-14 C, bromobenzene-1-14 C, and iodobenzene-l-14 C, and in deuterated bromobenzene it was found that the percentage of deuterium increased with percentage of reaction [505]. Fluorobenzene-2-D exchanged deuterium with the solvent very rapidly [506]. In dilute solution for partial reaction chlorobenzene-2-D showed a small increase in deuterium content, but showed a decrease in deuterium content in concentrated solutions.…”
Section: Solvolysis and The Effect Of Solvent On Ratessupporting
confidence: 78%
“…Early on, we were interested in probing the mechanism of this reaction and determining the critical factors necessary for its success. When the leaving group is a bromide, the deprotonation by LDA is likely to be the rate-determining step of the reaction , because elimination is fast and because of the low concentrations employed. The deprotonation is expected to initially generate a lithiated intermediate, which undergoes elimination to generate the aryne intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 2 Isotopic labelling experiments that support the intermediacy of arynes in the cine-substution of aryl halides by metal amide anions. The rate of reaction for the process 2→1 is dependent on X and generally follows the reactivity order Br > I > Cl >> F. The process by which the aryl halide 2 is converted to aryne 1 by a range of MNR 2 /HNR 2 systems (M = Li, Na, K; R 2 = H, Et and piperidyl) was investigated in detail by Huisgen 9 who studied the reaction kinetics, and by Roberts, 7,10 Bunnet 11 and Dunn 12 and their co-workers, who employed 2 H labelling techniques to study exchange and primary kinetic isotope effects. The kinetic and isotopic exchange behaviour was found to depend strongly on the identity of X, on the identity of R and on the concentration of HNR 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This advantage is somewhat outweighed by the requirement for a 1,2-difunctionalised precursor. Prior to conclusive demonstration that o-benzyne is symmetrical, 7,[9][10][11][12] Wittig had proposed that benzyne has a polarised (zwitterionic) structure (1c). This conclusion was not unreasonable based on his demonstration that benzyne can readily be generated from o-bromofluorobenzene by reaction with magnesium in tetrahydrofuran.…”
Section: Halogen-metal Exchangementioning
confidence: 99%